2018
DOI: 10.1002/1878-0261.12324
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses KRAS‐driven pancreatic cancer growth by inhibiting autophagy‐mediated energy metabolism

Abstract: Matrine is a natural compound extracted from the herb Sophora flavescens Ait which is widely used in traditional Chinese medicine for treating various diseases. Recently, matrine was reported to have antitumor effects against a variety of cancers without any obvious side effects; however, the molecular mechanisms of its antiproliferative effects on cancer are unclear. Here, we report that matrine inhibits autophagy‐mediated energy metabolism, which is necessary for pancreatic cancer growth. We found that matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…As a type of extract of Chinese traditional medicine radix sophorae flavescentis, researches had pointed out that MAT could induce cell apoptosis 26 and played a protective role in carcinoma. For instance, a research pointed out that MAT restrained cell proliferation in pancreatic carcinoma 27 while the other research pointed out that MAT restrained cell migration in lung carcinoma. 28 More interesting, in an animal model of bladder tumor, Gao et al pointed out that MAT could suppress bladder tumor invasion via regulation of the cyclooxygenase-2 (COX-2), and cytosolic recombinant phospholipase A2 (cPLA2).…”
Section: Discussionmentioning
confidence: 99%
“…As a type of extract of Chinese traditional medicine radix sophorae flavescentis, researches had pointed out that MAT could induce cell apoptosis 26 and played a protective role in carcinoma. For instance, a research pointed out that MAT restrained cell proliferation in pancreatic carcinoma 27 while the other research pointed out that MAT restrained cell migration in lung carcinoma. 28 More interesting, in an animal model of bladder tumor, Gao et al pointed out that MAT could suppress bladder tumor invasion via regulation of the cyclooxygenase-2 (COX-2), and cytosolic recombinant phospholipase A2 (cPLA2).…”
Section: Discussionmentioning
confidence: 99%
“…Matrine can inhibit the proliferation and migration of pancreatic cancer Panc-1 cells, induce ROS production, and induce apoptosis, which is related to ROS/NF-kB/matrix metalloproteinase (MMP) pathway (Huang and Xin, 2018). Matrine can also inhibit the proliferation of KRAS-mutated pancreatic cancer MIAPACA2 and 8988T cells, inhibit autophagy by downregulating STAT3, and inhibit mitochondrial energy production (Cho et al, 2018). Ma Y. et al (2015) reported that matrine downregulates the expression of MT1-MMP via Wnt signaling pathway and inhibits pancreatic cancer cell migration and invasion.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…For years, MT has been reported to have promising pharmaceutical efficacies for various cancer cells, such as acute myeloid leukaemia, nasopharyngeal Carcinoma, hepatocellular carcinoma, cervical cancer, colorectal cancer, bladder cancer, prostate cancer, pancreatic cancer. [43][44][45][46][47][48][49][50][51][52][53][54] However, the antitumor function about the molecular mechanism of MT still remains unclear. Like other extracts of botanicals, it has some moderate side effects, such as toxicity to the central nervous, coupled with system low water solubility, bioactivity and bioavailability.…”
Section: Matrinementioning
confidence: 99%